Perisylvian Functional Connectivity during Processing of Sentential Negation - Bahlmann, Jörg; Müller, Jutta L.; Makuuchi, Michiru; Friederici, Angela D. (Frontiers in Psychology, 2011)
Every language has the means to reverse the truth value of a sentence by using specific linguistic markers of negation. In the present study we investigated the neural processing costs afforded by the construction of meaning in German sentences containing negation in different clause types. We studied negations within and across clause boundaries as well as single and double negations. Participants read German sentences comprising of affirmations, single negations in the main or in the subordinate clause, or double negations. As a result, we found a network including the left inferior frontal gyrus (pars triangularis, BA 45), and the left inferior parietal gyrus (BA 40) to be activated whenever negations in the main clause had to be processed. Additionally, we found increased functional coupling between the left pars triangularis (BA 45), left pars opercularis (BA 44), left SMA (BA 6), and left superior temporal gyrus (BA 42) during the processing of main clause negations. The study shows that in order to process negations that require semantic integration across clause boundaries left BA 45 interplays with other areas that have been related to language processing and/or the processing of cognitive demands and logical/conditional reasoning. Thus, the results indicate that the left perisylvian language network synchronizes in order to resolve negations, in particular, whenever requirements on meaning integration are enhanced.